Study of a U-tube heat exchanger using a shape-stabilized phase change backfill material. (3rd April 2017) - Li, Xiangli; Tong, Cang; Duanmu, Lin; Liu, Liangkan
Abstract : This article describes the use of FLUENT software to simulate the heat transfer performance of U-tube heat exchangers in the ground source heap pump using the backfill materials of shape-stabilized phase change materials and crushed stone concrete. In this study, the shape-stabilized phase change material is a mixture of decanoic acid and lauric acid with the following mass concentration compositions: decanoic acid = 60%, silica = 10%, and expanded graphite = 6%. The mixture of shape-stabilized phase change material has a coefficient of thermal conductivity of 1.528 W/(m·K) and a latent heat of 109.2 kJ/kg. From the results of a 12-h simulation of the heat transfer dynamics, the heat exchange for a unit borehole depth of backfilling with shape-stabilized phase change material is 1.223 times the heat exchange for a unit borehole depth of backfilling with crushed stone concrete. In addition, the thermal influence radius of the backfill materials of shape-stabilized phase change material is 0.9 times of that of crushed stone concrete. As a result, under the same area of the buried pipes region, the shape-stabilized phase change material backfill can achieve a heat exchange 1.359 times that of crushed stone concrete backfill. Meanwhile, using shape-stabilized phase change material could contain the sustaining decline in coefficient of performance of heat pump at refrigerate condition to a certain extent and the appropriate physical parameters of phase change materials are also crucial.